Impact Test Value of Asphalt Composite with Bamboo Fiber Apus (Gigantochloa apus) - Frisko Yulian Maheswara; Januar Putra Umba Kusairiawan; Akhmad Basuki Widodo (Institut Teknologi Sepuluh Nopember, 2022)
The use of Fibrous Reinforced Plastic material with fiberglass reinforcement materials is considered to impact the environment and human health, giving rise to the idea of developing asphalt composite materials with fiber apus (Gigantochloa apus), which assessed can be the correct answer as an environmentally friendly material. Asphalt composite material with bamboo fiber apus is tested using the Charpy type impact test method by referring to ASTM to determine the substantial value of its impact. The value of the material impact test results is analyzed using the ANOVA method and compared to the impact test value of Bamboo Reinforced Plastic. The impact test results obtained that the highest value of the strong material impact of 5.9 J/cm² and the lowest by 0.1 J/cm², based on the results of the impact test, asphalt composite material with bamboo fiber content has not been able to exceed the highest value of bamboo reinforced plastic impact strength.